Terra do Sal: Projeto de um museu do sal em Praia Seca, Araruama, RJ - João, Cristiane Ramos Vianna (2012)
The present thesis proposes the creation of a Museum of the Salt at the location of Praia Seca, City of Araruama, Rio de Janeiro. The Museum aims to search and communicate the memories about the knowledge and expertises of the salt-making activity and the history of the formation of the Praia Seca locale. Intends to encompass the principles of the New Museology regarding its integration plan to the environment and the active participation of the community of Praia Seca. The acquis will mainly be formed by testimonials from different actors who participate in the history of the salt-making activity at Praia Seca, using the oral history as methodology. Our goal is the Museum of the Salt become a 'place of memory', besides its relationship with the city come to contribute to the appreciation of the memories and the writing of the local history as well as the development and dynamism of that locale.